Pre-epithelialized cryopreserved tracheal allograft for neo-trachea flap engineering - Zeng, Ning; Chen, Youbai; Wu, Yewen; Zang, Mengqing; Largo, Rene D.; Chang, Edward I.; Schaverien, Mark V.; Yu, Peirong; Zhang, Qixu (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Tracheal reconstruction presents a challenge because of the difficulty in maintaining the rigidity of the trachea to ensure an open lumen and in achieving an intact luminal lining that secretes mucus to protect against infection. Methods: On the basis of the finding that tracheal cartilage has immune privilege, researchers recently started subjecting tracheal allografts to “partial decellularization” (in which only the epithelium and its antigenicity are removed), rather than complete decellularization, to maintain the tracheal cartilage as an ideal scaffold for tracheal tissue engineering and reconstruction. In the present study, we combined a bioengineering approach and a cryopreservation technique to fabricate a neo-trachea using pre-epithelialized cryopreserved tracheal allograft (ReCTA). Results: Our findings in rat heterotopic and orthotopic implantation models confirmed that tracheal cartilage has sufficient mechanical properties to bear neck movement and compression; indicated that pre-epithelialization with respiratory epithelial cells can prevent fibrosis obliteration and maintain lumen/airway patency; and showed that a pedicled adipose tissue flap can be easily integrated with a tracheal construct to achieve neovascularization. Conclusions: ReCTA can be pre-epithelialized and pre-vascularized using a 2-stage bioengineering approach and thus provides a promising strategy for tracheal tissue engineering.